Calculation, Deposit, and Reporting of Restaurant Tax at RM. Chinese Food Apiau - Tamuntuan, Sinta Debora; Wokas, Heince RN; Tangkuman, Steven J (Universitas Sam Ratulangi, 2024)
Restaurant Tax is a tax on the services provided by restaurants. The collection system uses a self assessment system where taxpayers are given the authority to calculate, deposit and report the amount of Restaurant Tax owed themselves. This research aims to find out whether calculations, deposits and reporting in RM. Chinese Food Apiau complies with applicable regulations based on Tomohon City Regional Regulation Number 8 of 2017. The research method used in this research is descriptive qualitative with a case study approach. Data was obtained through observations, interviews and documentation. Research results at RM. Chinese Food Apiau shows that the calculation of Restaurant Tax is in accordance with Tomohon City Regional Regulation Number 8 of 2017 with a tax rate of 10%. However, for payment and reporting of Restaurant Tax by RM. Chinese Food Apiau does not comply with Tomohon City Regional Regulation Number 8 of 2017 because taxpayers are still late in depositing and reporting Restaurant Tax.